Implementasi Prinsip Pembelajaran Kurikulum Merdeka Melalui Penerapan Model Pembelajaran PAI Berbasis Heart to Heart di SMA - Nining, Ayi (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
The purpose of this study is to determine the application of the heart-to-heart-based PAI learning model in the perspective of the implementation of the Merdeka curriculum. The learning model plays a role in the effectiveness of the learning process, especially in order to achieve the learning objectives of character education because assessment in the classroom is not only based on cognitive aspects. The research was conducted at SMA Negeri 1 Kota Cirebon using descriptive methods and qualitative approaches. Data collection techniques were carried out through observation, document review, interviews, and questionnaires prepared based on needs analysis involving as many as 158 students at SMA Negeri 1 Kota Cirebon as respondents. The results showed that the application of the heart-to-heart-based PAI learning model was in line with the learning principles in the Merdeka curriculum. Heart to heart-based PAI learning applies the following principles: a) designed by considering the current stage of development and level of achievement of students, in accordance with learning needs, and reflecting the diverse characteristics and development of students so that learning becomes meaningful and enjoyable; b) learning is designed and implemented to build capacity to be lifelong learners; c) the learning process supports the holistic development of students' competencies and characters; d) relevant learning, namely learning that is designed according to the context, environment, and culture of students, and involves parents and communities as partners; and e) continuous future-oriented learning.Keyword : Independent Curriculumt; Heart to Heart; Islamic Education